Elongation, Cooking Loss and Acceptance of Wet Noodles Substituted with Fennel Leaves Flour - Zaqiatul Muna, Rusdin Rauf dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Fennel leaves are composed of various components that are beneficial to health andprovide a distinctive flavor. The effort to increase fennel leaf consumption isthrough the processing of fennel leaf flour as an intermediate product which can besubstituted in noodle product. The purpose of the study was to evaluate theelongation, cooking loss and acceptance of wet noodles substituted fennel leafflour. The study used a complete randomized design, with 4 fennel leaf floursubstitution treatments, were 0%, 2.5%, 5% and 7.5%. Wet noodles were analyzedfor elongation, cooking loss and acceptance. The elongation and the cooking lossdata were analyzed using One-Way ANOVA at a level of 0.05, while theacceptance data were analyzed using non-parametric Kruskal-Wallis followed byDuncan test. The results indicated that there was the influence of fennel leavesflour substitution on tensile strength, strain, cooking loss and acceptance of wetnoodles. The highest tensile strength was shown by wet noodle substituted 2.5%fennel leaf flour, was 0.18N. The biggest strain was revealed by wet noodlesubstituted with 0% fennel leaf flour, was 58.65%. The lowest cooking loss of wetnoodle was given by the substitution of 2.5%, was 0.66%. The lowest cooking lossof wet noodle was given by the substitution of 2.5%, was 0.66%. The highestacceptance was displayed by wet noodles substituted 0% fennel leaf flour, followedby 2.5% substitution.Keywords: Acceptance, cooking loss, elongation, fennel leaves, noodles.